On Zyras sensu strictu in the East Palaearctic and Oriental regions III, with a focus on the Southeast of Continental Asia and the Sunda Islands (Coleoptera: Staphylinidae: Aleocharinae: Lomechusini) - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2017)
Species of the nominal subgenus of the lomechusine genus Zyras Stephens, 1835 of the southeastern Oriental region are revised. Eighteen species are (re-)described and/or illustrated, six of them for the first time: Zyras (Zyras) latibasalis spec. nov. (Java, tentatively recorded also from Laos), Z. (Z.) rutrilobatus spec. nov. (Laos), Z. (Z.) parvilobatus spec. nov. (Laos), Z. (Z.) hirtiventris spec. nov. (Laos, Vietnam), Z. (Z.) hlavaci spec. nov. (Malaysia: Pahang, Selangor), Z. (Z.) lunatus spec. nov. (Malaysia: Selangor). Eight synonymies are proposed: Zyras bryanti Cameron, 1943 = Z. mortuorum Pace, 1990, syn. nov., = Z. paederinus Pace, 2008, syn. nov.; Zyras nigerrimus Cameron, 1943 = Z. bartolozzii Pace, 2003, syn. nov., = Z. alboterminalis Pace, 2008, syn. nov.; Z. granulipennis Cameron, 1930 = Z. pervariolosus Pace, 2008, syn. nov.; Z. matangensis Cameron, 1943 = Z. daiaccorum Pace, 2008, syn. nov.; Z. montanus (Bernhauer, 1915) = Z. variolatus Pace, 2003, syn. nov.; Z. preangeranus Cameron, 1939 = Z. quadriterminalis Pace, 2008, syn. nov. One species is excluded from Zyras: Myrmedonota modiglianii (Cameron, 1925), comb. nov. Lectotypes are designated for Zyras elegantulus Cameron, 1939, Z. semirufus Cameron, 1939, and Z. flavus Cameron, 1939. Additional records of nine named species are reported. A key to the species recorded from the southeastern Oriental region and an updated catalogue of the species of the Palaearctic and Oriental regions are provided. The subgenus is currently represented in the Palaearctic and Oriental regions by a total of 122 described species. Twenty-two species have been recorded from Sunda Islands. The countries with the greatest diversity are China (46 named species), India (20), Indonesia (19), Malaysia (15), Thailand (14), Nepal (12), Laos (11), and Vietnam (8).Nomenclatural ActsZyras (Zyras) latibasalis spec. nov. – urn:lsid:zoobank.org:act:35276B1A-6492-4F55-8836-91058719625CZyras (Zyras) rutrilobatus spec. nov. – urn:lsid:zoobank.org:act:67BAD12F-50BC-4983-A8BC-363FA67F01F1Zyras (Zyras) parvilobatus spec. nov. – urn:lsid:zoobank.org:act:6DBB36A1-C12B-4FA1-B28E-55560D6645C6Zyras (Zyras) hirtiventris spec. nov. – urn:lsid:zoobank.org:act:73489C67-FB52-4B48-A2E1-BA1F1E55F45DZyras (Zyras) hlavaci spec. nov. – urn:lsid:zoobank.org:act:F5734436-CE49-4064-8A52-BC7DF9A0EE67Zyras (Zyras) lunatus spec. nov. – urn:lsid:zoobank.org:act:ACD6BAAB-FE21-415D-903F-1D2CDEFE0607